Analisis Tindak Tutur Lokusi pada Konten Review Handphone dalam Kanal YouTube GadgetIn - Tri Wulaningsih; Norma Hidayanti; Ni’matul Maula Fitriani; Sabrina Defti Maharani; Jihan Aina Nabila; Asep Purwo Yudi Utomo; Anggit Wicaksono (Pusat riset dan Inovasi Nasional, 2024)
This article aims to analyze the locutionary speech acts used in cellphone review content on the YouTube channel